2021
DOI: 10.1515/npprj-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological analysis of constrained in-plane compression of paperboard using micro-computed tomography Imaging

Abstract: Large deformations under in-plane compression of paperboard appear in forming processes like hydroforming, pressforming and deep drawing, but the mechanisms of deformation have not been studied on a micromechanical level. A constrained in-plane compression test is presented. This test allows for in-plane compression, buckling, wrinkling and compaction. The constrained compression test is realized using a DEBEN CT-500 in-situ tester for laboratory microtomography and synchrotron microtomography. Experiments wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Figure 9 shows, therefore, the difference FDiff.IPCTM between the total force FT.IPCTM and two times the friction force FF.IPCTM. The difference force FDiff.IPCTM and the in-plane compression force FIPC.IPCTM were almost exactly the same in terms of progression and amount, meaning that FIPC.IPCTM was measured without the influence of any friction forces in contrast to the results in Wallmeier et al (2021). The progression of the in-plane compression force FIPC.IPCTM increased steadily at the beginning of the IPCTM to a global maximum and then decreased to an almost constant plateau.…”
Section: In-plane Compressionmentioning
confidence: 68%
See 1 more Smart Citation
“…Figure 9 shows, therefore, the difference FDiff.IPCTM between the total force FT.IPCTM and two times the friction force FF.IPCTM. The difference force FDiff.IPCTM and the in-plane compression force FIPC.IPCTM were almost exactly the same in terms of progression and amount, meaning that FIPC.IPCTM was measured without the influence of any friction forces in contrast to the results in Wallmeier et al (2021). The progression of the in-plane compression force FIPC.IPCTM increased steadily at the beginning of the IPCTM to a global maximum and then decreased to an almost constant plateau.…”
Section: In-plane Compressionmentioning
confidence: 68%
“…9. To prove this hypothesis, future research should add a camera setup to the IPCTM to record the progression of the wrinkle formation in relation to the position of the metal sheet, similar to the approach described in Wallmeier et al (2021).…”
Section: In-plane Compressionmentioning
confidence: 99%
“…It was demonstrated that an increase in out-of-plane deformation is accompanied by a decrease in inter-fiber bonding. More recently, Wallmeier et al (2021) conducted a conceptual analysis of the restrained in-plane compression of cardboard using 𝜇CT imaging and the DVC method. This was done with the aim of improving understanding of in-plane compression, buckling, wrinkling, and compaction.…”
Section: Digital Volume Correlation (Dvc)mentioning
confidence: 99%
“…Analysis of such data have the potential to reveal active microscale mechanisms during in-situ compressive loading of paperboard, both qualitatively and quantitatively with image analysis. In a recent study by Wallmeier et al (2021), X-ray tomography was used to visualize and analyse in-plane compression mechanisms in paperboard, such as delamination and wrinkle formation. For out-of-plane compression of pressboard samples, Joffre et al (2015) used X-ray tomography and Digital Volume Correlation (DVC) to study material changes between the non-loaded and the maximum compressed state.…”
Section: Introductionmentioning
confidence: 99%